CSTF2 Promotes Hepatocarcinogenesis and Hepatocellular Carcinoma Progression via Aerobic Glycolysis - Chen, Zhimin; Hao, Weijie; Tang, Jingzhi; Gao, Wei-Qiang; Xu, Huiming (Frontiers in Oncology, 2022)
Background: Shortening of 3’ untranslated regions (3’UTRs) of mRNAs by alternative polyadenylation (APA) is an important mechanism for oncogene activation. Cleavage stimulation factor 2 (CSTF2), an important regulator of APA, has been reported to have tumorigenic function in urothelial carcinoma of the bladder and lung cancers. However, the tumor-promoting role of CSTF2 in hepatocellular carcinoma (HCC) and its underlying molecular mechanism remains unclear. Methods: We used multiple HCC databases to analyze CSTF2 expression in HCC and further studied the relationship between the expression levels of CSTF2 and prognosis. Function enrichment analysis was used to investigate the molecular mechanism of CSTF2 for the occurrence and development of HCC. The biological function in HCC cell lines in vitro was determined by CCK8, colony formation, transwell migration and invasion assay. Moreover, the tumorigenic function of CSTF2 in vivo was measured by subcutaneous tumor formation or injecting four plasmids into mouse tail vein within 5s-7s in an immunocompetent HCC mouse model. In addition, aerobic glycolysis in HCC cells was determined by measuring extracellular acid rate (ECAR) and extracellular glucose and lactate levels. Results: Bioinformatics analysis revealed that CSTF2 was overexpressed in HCC tissues. High expression of CSTF2 was correlated with a poor prognosis and high histological grades. CSTF2 knockout inhibited the proliferation, migration, and invasion of HCC cells. In addition, CSTF2 knockout HCC cells failed to form tumors by subcutaneous graft experiment. Furthermore, endogenous CSTF2 knockout attenuated hepatocarcinogenesis in an immunocompetent HCC mouse model. Function enrichment analysis suggested that high expression of CSTF2 was associated with enhanced glycolysis. Moreover, we found that CSTF2 knockout reduced the level of short 3’ UTR isoform of hexokinase 2 and increased its level of long 3’UTR. Furthermore, CSTF2 knockout inhibited ECAR levels, glucose uptake and lactate production. Conclusion: Our results indicated that CSTF2 is highly expressed in HCC and is correlated with a poor prognosis and high histological grade. Knockout of CSTF2 inhibits tumorigenesis and procession of HCC both in vitro and in vivo. Moreover, CSTF2 is associated with enhanced glycolysis. Therefore, this study suggests that CSTF2 might be a new prognostic biomarker and therapeutic target for HCC.